Social housing architecture and design - Broto, Carles (Links International, 2014)
The examples included in this volume are a clear demonstration of the optimization of resources used in social housing architecture. These projects offer a great variety of typological solutions that are as flexible in their material fulfillment as in their functionality. Every project in this book is thoroughly documented and profusely illustrated with full-color photographs, offering a wealth of information for architects, students, or anyone else who is interested in new forms of social housing architecture.